The impact of business cycle on Pakistani banks capital buffer and portfolio risk - Venus, Khim-Sen Liew; Rossazana, Binti Ab-Rahim; Samina, Riaz (Institute for Economic Forecasting (IEF), 2019)
This study attempts to estimate the impact of business cycle on Pakistani banks capital buffer and portfolio risk. Dynamic Panel data model, which includes a set of control variables reflect bank characteristics, has been estimated by using two-step Generalized Method of Moments (GMM) during the period of 2004-2014. The main results exhibit that bank capital buffer fluctuates counter-cyclically but business cycle fluctuations have no significant impact on portfolio risk. The main results support to Basel III accord that capital conservation buffer and counter-cyclical capital buffer are essential for banking institutions to help the economy. This study departs from existing literature because it focuses on developing country in assessment of behavior of capital buffer in a cyclical manner. The study contribute to the existing literature by revealing that counter-cyclical fluctuation of capital buffer may be due to shortsightedness of banks or low loan demand during downturns. This study will help policy makers to make and implement viable decisions on the optimal capital buffers and policy maker will seize an opportunity to devise strategies to ensure that banks have a sufficient buffer built up at all times to help protect the banks, their depositors and the economy at large. © 2019, Institute for Economic Forecasting. All rights reserved.